MEDIATION IN POLISH LABOUR LAW: COMPARING ITS EVOLUTION AND DEVELOPMENT TO LABOUR MEDIATION IN EU AND US LAW - Antolak-Szymanski, Katarzyna (Review of European and Comparative Law, 2018)
Mediation was popularized in modern times in the United States. Its origins were found in the mediation of labour disputes between unions and employers, as a means of avoiding strikes, and currently it is used more and more frequently in individual employment matters. While mediation is not as widespread in Poland to date, its use in labour and employment cases appears to have a similar arc of development. Since the 1990s, mediation has had a central and positive role in resolving collective labour disputes, and now it is being used increasingly in individual employment cases. This paper explains these developments, with a particular focus on the evolution and scope of employment mediation under Polish and European Union law. The author concludes that although the basic framework exists for mediation to develop further in Poland, further reforms would be helpful to ensure its success.